The Role of Age and Imaginative Play as Predictors of Cognitive Flexibility in Preschool-Aged Children - Putri, Atika Rahma; Djuwita, Efriyani; Wiswanti, Inge Uli (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Cognitive flexibility is a part of executive function that helps individuals adjust to changing circumstances, which is important for children to adapt with surroundings. Alongside with rapid cognitive development during preschool-age, preschoolers also show maturity in symbolic functions that grow distinct characteristics in imaginative play. This research aimed to see the role of age and imaginative play in predicting preschool-aged children's cognitive flexibility. Sample was carried out using a convenience-sampling technique and this research subjects were 74 preschoolers (4–6 years) and their parents. Participants in this study are preschool-aged children who are enrolled at preschool in Jakarta, Bogor, and Depok areas, along with parents or guardians of the children who accompanied the children in their daily activities at home. This study used hierarchical linear regression analysis techniques in SPSS to analyze the role of age and imaginative play in predicting cognitive flexibility. The result showed both age and imaginative play significantly predict cognitive flexibility. Age has 9.4 percent of the role, whereas imaginative play accounted for 8.3 percent. These provide an illustration for parents and educators that imaginative play activities can facilitate the development of cognitive flexibility at preschool age.